Efficacy of the Sander bite‐jumping appliance in growing patients with mandibular retrusion: a randomized controlled trial. (7th January 2013) - Martina, R.; Cioffi, I.; Galeotti, A.; Tagliaferri, R.; Cimino, R.; Michelotti, A.; Valletta, R.; Farella, M.; Paduano, S.
Structured Abstract Objectives The efficacy of functional appliances remains highly debated. This randomized controlled trial investigated the skeletal and dentoalveolar effects determined by the Sander bite‐jumping appliance (BJA). The null hypothesis to be tested was that the appliance would not induce supplementary mandibular growth compared to untreated controls. Setting and Sample Population This study was carried out at the Section of Orthodontics, University of Naples Federico II, Italy. Forty‐six patients receiving a clinical diagnosis of skeletal and dental class II due to mandibular retrusion were either allocated to a treatment (23 patients;15 boys, 8 girls; mean age ± SD: 10.9 ± 1.3 years) or to an untreated control group (23 patients;11 boys, 12 girls; mean age ± SD: 10.5 ± 1.2 years), by using a balanced block randomization. Methods Lateral cephalograms were taken before and after treatment and used for comparisons. Measurements were analyzed by descriptive statistics, univariate and multivariate statistical tests. Results Treated individuals had a significant increase in mandibular length (6.4 ± 2.3 vs. 3.5 ± 2.5 mm; p < 0.001), overjet reduction (−5.0 ± 2.9 vs. 0.3 ± 1.2 mm; p < 0.001) and molar relationship improvement (−5.3 ± 2.4 vs. 0.1 ± 1.1 mm; p < 0.001) compared to controls. The use of the appliance did not significantly affect jaw divergence. Proclination of lower incisors was slightly greater (3.0°, p = 0.023) in treated patients than in controls. The increase in mandibular length was not significantly influenced by cervical stage (p = 0.40). Conclusion The BJA can effectively correct class II malocclusions by a combination of dentoalveolar and skeletal effects. The long‐term stability of the correction needs to be evaluated.